The Capacitated Sustainable EOQ Models: Models Considering Tax Emissions - Maulana, Sri Kurnia Dwi Budi; Utama, Dana Marsetiya; Asrofi, Mochammad Samsul; Ningrum, Inggit Sekar; Alba, Nidaul; Ahfa, Hikam Antasyard; Zein, Thoriq Akbar (Department Industrial Engineering, University of Muhammadiyah Malang, 2020)
The study investigated problems of determining the lot size by considering sustainability and capital constraints for purchasing raw materials and taxes. By using the Sustainable EOQ (SEOQ) models that considered environmental aspects, the researchers also evaluated the capital constraints. The proposed models were used to minimize total inventory costs. In this study, there was a practical numerical analysis and sensitivity analysis to help decision-makers and policies on inventory problems. Finally, the experimental results showed that the proposed models were effectively used to solve the problems.